Exploring the challenges, needs and coping strategies of malay working single mothers in Klang Valley, Kuala Lumpur - Sakinah Salleh (Institute of Education, International Islamic University Malaysia, 2015)
Becoming a single parent may be the results of divorce, death of a husband or wife. The rise in the percentage of the single parents among Malay Working Single Mothers (MWSMs), in Malaysia has brought with itself an unavoidable need to investigate the area. The challenges faced by them give impact to their own and their children's well-being requires professional help. Hence, a study on single working parent is necessary. This study focused on the challenges, needs and coping strategies of the MWSMs. The qualitative case study was employed in this study because the aim was to explore the needs of the MWSMs, in Malaysia. A case study approach is appropriate for this research, because the aim is investigating the 'how'. At the same time, this case study is concerned with studying a particular need or challenge and solution, in relation to a specific group. In this study, the details have been derived through individual interviews with 10 MWSMs, chosen from Klang Valley. Findings from this study highlighted several major themes namely psychological problems related to the Malay working single mothers, child upbringing issues, the work-family conflict, financial constraints, childcare and education, professional guidance and consultancy and also masculine technical support. These issues strengthened their self-efficacy and resiliency, improved their Islamic spiritual coping skills and widened their social support systems. The noble aspect of this research is that the study address the gap in studies related to MWSMs in Malaysia, which can be helpful to MWSMs, themselves. Support, in terms of internal and external coping strategies, advised to MWSMs, can prove a positive influence on their personal and their children's well-being. The findings also provide some insight to policy makers and the society on the identification of the underlying issues that enables these women to seek appropriate help and enables the government agencies and non-governmental organizations to plan for suitable intervention programs and provide adequate support and assistance.